Microscopic understanding of the anisotropic conductivity of PEDOT:PSS thin films - Mantovani Nardes, Alexandre; Kemerink, Martijn; Janssen, René A. J.; Bastiaansen, Jolanda A. M.; Kiggen, Nicole M. M.; Langeveld-Voss, Bea M. W.; Breemen, Albert J. J. M. van; de Kok, Margreet M. (Advanced materials, 2007)
The anisotropic conductivity of thin films of poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is correlated to the film morphology as obtained from scanning tunneling and atomic force microscopy images. The material was found to consist of layers of flattened PEDOT-rich particles that are separated by quasi-continuous PSS lamella (see figure).